2019
DOI: 10.15587/2519-4984.2019.177106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of value clarification technique (VCT) learning model on homeland attitude at elementary school

Abstract: Це дослідження має за мету вивчити вплив учбової моделі Техніки Виявлення Цінності на відчуття любові до Батьківщини на четвертому ступені початкової школи або SekolahDasar (SD) в Індонезії. Дослідження було здійснено в мікрорайоні SD Negeri 1 Karangmoncol PurbalinggaKarangsari, використовуючи квазі-експериментальне дослідження на прикладах нееквівалентного дизайну контрольної групи. Це дослідження використовує дві групи: експериментальну-із застосуванням учбової моделі Техніки виявлення цінності та контрольну… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The assumption that occurs in children, namely the existence of moral deviations is an indication that affective values do not take root in the soul or heart of the child. This phenomenon does not only occur in other countries but also in our country, such as the decline in morality seen in our youth [2]. Characteristics of early adolescence presented by Daradjat, Z, After the 12-year-old child (grade VI) moved from childhood which was known to be calm, not much debate and questions, they entered a period of shock, because of their rapid growth in all fields, their feelings of turmoil were unstable.…”
Section: Introductionmentioning
confidence: 72%
“…The assumption that occurs in children, namely the existence of moral deviations is an indication that affective values do not take root in the soul or heart of the child. This phenomenon does not only occur in other countries but also in our country, such as the decline in morality seen in our youth [2]. Characteristics of early adolescence presented by Daradjat, Z, After the 12-year-old child (grade VI) moved from childhood which was known to be calm, not much debate and questions, they entered a period of shock, because of their rapid growth in all fields, their feelings of turmoil were unstable.…”
Section: Introductionmentioning
confidence: 72%
“…The results of the research showing the advantages of implementing the VCT strategy include research by (Ima et al, 2023;Nirmayani & Yudiana, 2023;Yusrizal & Hariati, 2022) which concluded that the VCT learning activity strategy can evoke an understanding of the value of appreciating hero service. The results of experimental research (Asikin et al, 2021;Dewantoro & Sartono, 2019;Ula et al, 2020) show the VCT method's superiority over conventional methods, which concludes that the VCT model can improve student character. Research (Merian et al, 2019) concluded that various VCT methods can develop students' moral knowledge, behavior, and independence.…”
Section: Values Clarification Technique (Vct)mentioning
confidence: 99%
“…Siswa tampak memiliki rasa percaya diri pada saat proses pembelajaran, seperti berani mengemukakan pendapat dan bertanya melalui pembelajaran Value Clarification Technique (VCT). Kemudian, penyampaian materi pembelajaran yang dikaitkan dengan kehidupan sehari-hari membuat siswa bersemangat mengikuti proses pembelajaran (Dewantoro & Sartono, 2019;Ermawati et al, 2021). Pada saat guru menyampaikan materi, siswa dituntut selalu memperhatikan gurunya.…”
Section: Pembahasanunclassified